Differences in androgens of HIV positive patients with and without Kaposi sarcoma. Issue 6 (June 1995) - Christeff, N; Winter, C; Gharakhanian, S; Thobie, N; Wirbel, E; Costagliola, D; Nunez, E A; Rozenbaum, W
Abstract : AIM–Since most forms of Kaposi sarcoma are much more common in men than in women, the aim of this study was to examine serum concentrations of sex steroids in HIV positive men with and without Kaposi sarcoma. METHODS–Blood samples from 34 HIV positive men without Kaposi sarcoma (KS-) and 28 with Kaposi sarcoma (KS+) and from 35 HIV negative men (controls) were analysed for adrenal and gonadal steroids. Further analysis was done in subgroups classified by CD4 lymphocyte counts. RESULTS–KS+ patients had significantly higher serum dehydroepiandrosterone (DHEA) and testosterone concentrations than the KS- patients, and their DHEA, DHEA sulphate, testosterone, and androstenedione values were higher than in the controls. The KS+ patients with more than 500 CD4 lymphocytes per mm3 had significantly higher serum DHEA, DHEA sulphate, and testosterone than the KS- patients with the same CD4 counts; those with 500-200 CD4 cells/mm3 had higher serum DHEA and testosterone than the equivalent KS- men; and those with < 200 CD4 cells/mm3 had raised DHEA only compared with KS- men. Both KS+ and KS- men had higher serum progesterone and oestradiol than the controls. Glucocorticoids were not significantly altered. CONCLUSIONS–The high androgen levels in KS+ patients, particularly in the early stages of the disease (> 500 CD4 cells/mm3), may affect the immune system by inducing an abnormal cytokine profile, or by increasing T8 proliferation and activation, or both. This raises the question of the relationship between androgens and Kaposi sarcoma.